2013
DOI: 10.1089/jpm.2013.0038
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Caregivers of Terminally Ill Cancer Patients: Impact on Their Perspective of the Patients' Symptom Burden

Abstract: Integrative palliative care should offer psychooncological care for the caregivers on a routine basis to avoid misleading perspectives possibly influencing end-of-life treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 29 publications
5
38
0
2
Order By: Relevance
“…Our findings are consistent with previous research that suggests a high prevalence of anxiety and depression in family caregivers of palliative patients in home-based care (Cora et al, 2012;Oechsle et al, 2013;Payne & Grande, 2013;Pitceathly & Maguire, 2003). Our findings are consistent with previous research that suggests a high prevalence of anxiety and depression in family caregivers of palliative patients in home-based care (Cora et al, 2012;Oechsle et al, 2013;Payne & Grande, 2013;Pitceathly & Maguire, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with previous research that suggests a high prevalence of anxiety and depression in family caregivers of palliative patients in home-based care (Cora et al, 2012;Oechsle et al, 2013;Payne & Grande, 2013;Pitceathly & Maguire, 2003). Our findings are consistent with previous research that suggests a high prevalence of anxiety and depression in family caregivers of palliative patients in home-based care (Cora et al, 2012;Oechsle et al, 2013;Payne & Grande, 2013;Pitceathly & Maguire, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Providing care at home can itself be a source of stress, which in palliative situations is increased by awareness of a terminal diagnosis. Because of the physical and emotional burden of care, they often suffer from distress (Ando, Ninosaka, Okamura, & Ishi, 2013;Götze, Brähler, Gansera, Polze, et al, 2014;Oechsle, Goerth, Bokemeyer, & Mehnert, 2013). Because of the physical and emotional burden of care, they often suffer from distress (Ando, Ninosaka, Okamura, & Ishi, 2013;Götze, Brähler, Gansera, Polze, et al, 2014;Oechsle, Goerth, Bokemeyer, & Mehnert, 2013).…”
Section: Family Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors indicated that cancer care affects all aspects of the cancer patient and patient's family including psychological, physical, social, financial and spiritual well-being (Girgis & Lambert 2009;Stenberg et al 2010;Lee et al 2013). Thus, while the prevalence of anxiety and depression among cancer caregivers ranges from 10% to 53%, the ratio among partners of cancer patients ranges from 16% to 56% (Raveis et al 1998;Kozachik et al 2001;Girgis & Lambert 2009;Stenberg et al 2010;Lee et al 2013;Oechsle et al 2013;Utne et al 2013). Girgis and Lambert (2009) have reported that caregivers of cancer survivors experience social and personal loss.…”
Section: Introductionmentioning
confidence: 99%
“…Como consequência, a própria assistência prestada pode ter sua qualidade afetada. Habitualmente representado pelo segmento leigo, numa condição de assistência informal, o cuidador assume novas responsabilidades, de maneira que a sobrecarga de trabalho, o tempo insuficiente para o lazer e para o cuidado com sua própria saúde irão apresentar fatores de risco para o desenvolvimento de depressão e ansiedade (12)(13) . Ademais, a sobrecarga está correlacionada diretamente com o estado geral de saúde do cuidador, de modo que aspectos emocionais, psicológicos e financeiros tendem a estar abalados (14)(15)(16) .…”
unclassified